Konut fiyatlarının çok kriterli bir karar destek modeli ile tahmin edilmesi - Kavas, Seçil (Fen Bilimleri Enstitüsü, 2014)
Belirli bir arazi ve bu arazi üzerinde insanlar tarafından yapılmış olan yapıların tamamı "gayrimenkul" olarak nitelendirilir. "Gayrimenkulün değeri" ise değerleme anı itibari ile mal sahibinin taşınmazdan elde edebileceği faydaya ilişkin piyasanın genel görüşünü ifade eden bir değerdir. Gayrimenkullerin para cinsinden değerine bir çok iş alanında ihtiyaç duyulmaktadır. Alım, satım işlemleri, sigortalama, ipotek, yatırım işlemleri gibi işlemlerde gayrimenkulün para cinsinden değeri üzerinden işlemler gerçekleştirilir. Gayrimenkuller aynı zamanda bir ticaret aracı olarak da kullanıldıkları için doğası gereği değerleri sabit değildir. Gayrimenkullerin sahip olduğu özelliklere, konumuna, gayrimenkulün yer aldığı pazara, piyasadaki arz/talep dengesine göre gayrimenkulün değeri değişken bir trend izlemektedir. Bu açıdan bakıldığında, gayrimenkul fiyatının belirlenmesi, bir çok değişken ve kısıtı bir arada barındıran kompleks bir problemdir. Bu çalışma kapsamında, gayrimenkul tipi "konut" olan taşınmazların sahip oldukları fiziksel, yapısal ve çevresel özellikler ile pazar özelliklerini göz önüne alan bir karar destek modeli oluşturularak, konut fiyatlarının gerçeğe en yakın şekilde tahmin edilmesi amaçlanmıştır. Çalışma temel olarak iki aşamadan oluşmaktadır. İlk kısımda konut fiyatlarının belirlenmesinde etkili olan değerlendirme kriterleri belirlenmiştir. İkinci aşamada ise belirlenen kriterler üzerinden bir karar destek modeli oluşturulmuştur. Değerlendirme kriterlerinin belirlenmesi kısmında ilk olarak literatürde konut fiyatlarının tahmini üzerine yapılan çalışmalar incelenmiş ve bu çalışmalarda konut fiyatlarını tahminlemede kullanılan değerlendirme kriterleri saptanmıştır. Sonrasında, gayrimenkul değerleme uzmanları ile görüşülerek, bir konutun fiyatının belirlenmesinde önemli görülen değişkenler öğrenilmiştir. Literatür araştırması ve eksper görüşlerinden elde edilen kriterler bir araya getirilerek, konut fiyatlarının tahmininde dikkate alınabilecek olan 84 kriterlik bir değerlendirme havuzu oluşturulmuştur. Havuzda yer alan kriterlerden hangilerinin seçilen belirli bir bölgedeki konut fiyatlarının tahmininde aktif bir değişken olacağına karar vermek üzere, öncelikle manuel, sonrasında ise regresyon analizi yardımı ile kriterler değerlendirilmiştir. Uygulama bölgesi olarak İstanbul, Beşiktaş ilçesi seçilmiştir. İlçede '01.01.2010' tarihinden sonra değerleme uzmanları tarafından fiyat tespiti yapılmış, %100 oranında inşaatı tamamlanmış ve gayrimenkul tipi "konut" olan taşınmazlar üzerinden analiz çalışması yürütülmüştür. Uygulama yerinin seçiminin ardından, ilk olarak bölgedeki tüm konutlar için ortak olan özellikler belirlenerek, elenmesi gerekli görülen kriterler, eksper görüşlerine de başvurularak havuzdan çıkarılmıştır. Sonrasında havuzda kalan değerlendirme kriterleri için regresyon analizi uygulanmıştır. Seçilen bölgede yer alan 1168 konutun değerleri üzerinden yapılan regresyon analizi sonucunda, bölgede konut fiyatlarının belirlenmesinde aktif rol oynayan 11 kriter belirlenmiştir. Çalışmanın ikinci kısmında belirlenen kriterleri girdi olarak kullanan bir karar destek modeli oluşturulması hedeflenmiştir. Bu modelde amaç, bölgede yer alan bir konutun fiyatının, sahip olduğu özelliklere dayandırılarak tahmin edilmesidir. Konutların sahip oldukları özellikler üzerinden bir puan hesaplanarak, belirlenen puana göre konutun fiyatının ortaya konulan model dahilinde hangi fiyata karşılık geleceği tahmin edilecektir. Bu amaçla Beşiktaş ilçesindeki örneklem havuzunda yer alan 1168 konut %70-%30 oranında rassal olarak 2 gruba ayrılmış, model ve test havuzları oluşturulmuştur. %70'lik dilimde yer alan 818 konut model havuzunu oluşturmaktadır. Bu konutlar için belirlenen 11 kritere göre aldıkları değerler üzerinden normalizasyon yapılmış ve konutların her bir kriter için aldığı değer, boyutlarından arındırılarak belirlenmiştir. Kriterlerin konut fiyatının belirlenmesinde farklı ağırlıklara sahip oldukları tahmin edilmektedir. Kriterlerin ağırlıklarını belirlemek üzere analitik hiyerarşi süreci (AHP) uygulanmış ve her bir kriterin konut fiyatını belirlemedeki etkisi ikili karşılaştırma matrisleri yardımıyla saptanmıştır. AHP sürecinde öncelikle 11 kriter özelliklerine göre 5 ana gruba ayrılmıştır. Gayrimenkul değerleme uzmanlarından bu 11 kriteri, önce ait oldukları gruplara olan etkilerine göre, sonrasında ise bu ana grupların, konut fiyatının belirlenmesindeki etkilerine göre ikili olarak karşılaştırmaları istenmiştir. Sürecin sonunda her bir kriterin ayrı ayrı, konut fiyatını belirlemedeki ağırlıkları saptanmıştır. Konutların her bir kriter için normalize edilmiş değeri ile, ilgili kriterin ağırlığı çarpılarak, konutun ilgili kriterden elde ettiği puan belirlenmiştir. Sonrasında tüm kriterler için hesaplanan bu değerler toplanarak, konutun nihai puanı belirlenmiştir. Bu aşamanın sonucunda elimizde model havuzunda yer alan her bir konut için konut puanı ve satış değeri bilgisi mevcuttur. Konutlar için elde edilen bu iki bilgi üzerinden grafik oluşturularak değerlerin dağılımları gözlemlenmiştir. Puan-fiyat ikililerinden faydalanarak, trendi temsil eden doğru ve eğri denklemleri belirlenmiştir. Bu denklemler, yeni konutlar için fiyat tahmini yapılmak üzere kullanılacaktır. Buna göre yeni bir konutun fiyatı belirlenmek istendiğinde öncelikle konutun 11 kritere göre aldığı değerler üzerinden konutun puanı hesaplanacaktır. Sonrasında hesaplanan puan denklemde ilgili bağımlı değişkenin değeri olarak atanacak ve konutun satış fiyatı tahmin edilecektir. Yapılan çalışmada geliştirilecek olan model yardımıyla, konut fiyatlarını belirlemede göz önüne alınması gereken değişkenler ve bu değişkenlerin konut fiyatını etkileme ağırlıklarının saptanması, değerleme sırasındaki değerleme uzmanının bilgi ve beceri seviyesine olan bağımlılığın minimize edilmesi ve değerleme sürelerinin kısaltılması hedeflenmiştir.

Certain land as well as buildings that have been made by people all over this land is considered as "real estate". After using real estates as a trading good, "the value of the property" concept has been born. "Value of the property" term can be explained as the benefit to be obtained by the owner of the property at the time in the market. Since the transaction aim of the property is not only for residential but also for commercial, the value of the real estates is unstable in the market. It varies according to features and the specialties of the real estate, willingness to buy/sell and so on. So, to avoid the mistakes on appraising process, there is need of reliable and widely accepted methods to appraise the value of real estate. There are three commonly used methods of assessment that have been determined in accordance with international standards. They are "peer comparison", "discount cash flow analysis" and "cost approach". Peer comparison is the most widely used and accepted method of valuation, that is used by professional experts in the real estate market. Peer comparison approach takes into account the substitutes of a given property. This approach utilizes the current market value of substitute properties and tries to estimate the value of a subjected property. This method is useful for a region in which it is easy to find peers as well as peer's selling prices. In this method, as the number of peers increase, the valuation of the property, which is the subject of valuation, gets closer to the true value. Since most of the time it cannot be possible to find an exactly the same peers of a given property, it is better to use price for square meter or "net income multiplier" – a multiplier that can be obtained by dividing the value of selling price to net income – to compare. Discount cash flow analysis calculates the current time value of expected incomes and expenses of a given property. It is used in lack of finding enough peers in a given zone. On the other hand, third method, cost approach, considers the costs in the case of the reconstruction of the same property. It takes into account the money should be spent, land costs, reconstruction costs and depreciation values to estimate the value of a given property. Potential downside of this method is misapprehension of the values because of not considering the market fluctuations. Besides these methods, there are several approaches which seek an appropriate method to estimate the most accurate value of properties. Since the currency value of a property is unstable and cannot be explained just by the features of the building or neighborhood area, valuation of the property can be described as a complex problem with many parameters and constraints. There are several studies in the literature, which seek an appropriate model to appraise the value of the property. Pagourtzi and others have been divided these methods in two groups: "traditional methods" and "advanced methods". Peer comparison method, which has commonly wide usage in the residential market, investment/income method and multiple regression method can be counted as examples of "traditional methods". The models, which simulate the stakeholders' mental model in the market for appraising, are called as an "advanced models". Artificial neural networks, hedonic pricing methods and fuzzy logic models are the examples of advanced models. In the literature, most of the studies which are conducted with appraising of residential property have utilized the hedonic methods. This method is useful for establishing a relationship between the criteria and the value of the property. But before conducting a relationship between criteria and value of the property, it is important to identify and select the criterion which has meaningful effect on valuation process. The initial studies in this area began in the mid-1960s. Alonso, 1964, claims that a neighborhood of the trade centers is a key value for defining the value of the property. After Alonso, Muth, 1969, Kain & Quingley, 1970, Adair et al, 2000, Din et al, 2001, Fan et al, 2006 did research on defining the criteria. Rossini, 1997, has claimed that, the criteria like transaction value, area, number of rooms, and year of constructions do not contain qualitative characteristics. On the other hand, style of the buildings, neighborhood area, common areas of the interest zone are the basic and strong criteria on evaluating property but mostly there is no sufficient information about these types of qualitative criteria. The objective of this paper is to present a decision support model that estimates the value of a residential property according to its structural, physical, environmental and market features. Basically, the study consists of two main stages. At the first stage, the evaluation criteria that are influential on appraising process of residential real estates have been identified. At the second stage, a decision support model which has used the idetified criteria to appraise a residential real estate, has been built. Firstly, the review of the literaure has been performed to identify the criteria that have impact on appraising process. The evaluation criteria which are commonly used in the literature to determine the characteristics of the residential property have been identified. Then, judgments of the experts from the residential market are collected. The literature outcomes and expert views have been aggregated and customized according to focused problem. As a result, "criteria pool" with 84 ciretia that will be used in appraising a given residential property, is identified. To be more clear, criteria pool must be specialized according to focused zone. In this study, researches have been conducted in the Beşiktaş (İstanbul) district. Firstly, manuel verification has been done on criteria pool to eliminate some nonrelevant criteria, because of the selected zone's characteristics. After that, regression analysis was performed to identifiy the final criteria that will be used in decision suppert model. As a result of regression analysis, 11 criteria, which have an significant effect on residential prices, have been selected. After structuring the final criteria pool, the next stage is prioritizing the criteria. For this purpose, pairwise comparison judgments of the experts are assessed. The performance values of zones as well as residential properties are received based on expert judgments and objective evaluations. Finally, global rating scores, which can be expressed as estimated values of residential properties, are calculated. At the second stage of the study, it is aimed to develop a decision support model which uses the identified criteria as input. The main purpose of the model is to appraise a given residential real estate accurately. To achieve this, scores of the house according to 11 criteria have been calculated. 1168 houses in Beşiktaş were randomly divided into 2 groups (70%-30%): First group with 818 individulas is the sample pool and second group with 350 individuals is testing pool. Each house's score according to 11 criteria are normalized to compare with each other. Criteria for determining housing prices are estimated to have different weights. So, analytical hierarchical process has been conducted to identify the weights of the each criteria. Pairwise comparison questions for 11 criteria have been formed and real estate evaluation experts are questioned to identify the preferential criteria and their weights according to main purpose. After defining the weight of the impact on main purpose for each criterion, "performance score" for each house in the sample pool has been calculated by multiplying the houses's criteria score and weight of the related criteria. As a result, the score and selling price for each houses in the sample pool have been put together. The trend graphics have been plotted according to these two variables. These trend lines/curves will be used to appraise a selling price of the new comers. The decision support model which will be introduced in this study, will guide valuation experts to focus on the important evaluation criteria and to take into consideration the criteria according to their speified weights. By the help of this model, it is aimed to reduce the dependence on valuation experts' abilities, during the valuation process.
Multi-criteria decision support model for appraising residential real estates
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2014
Keywords: AHP ,Doğrusal olmayan regresyon , Çok kriterli karar verme , Çoklu lineer regresyon analizi; AHP , Nonlinear regression ,Multi criteria decision making , Multiple linear regression analysis